Automatic Light Control System for Bathroom Using Arduino Uno - Ripo Winda Kusuma; Delsina Faiza; Thamrin; Sartika Anori (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This study aims to design and develop an Arduino Uno microcontroller-based automated system for controlling lighting and ventilation to minimize energy waste associated with user inattention in deactivating electronic devices. Using a Passive Infrared Receiver (PIR) sensor, the system detects human presence within a room and automatically activates or deactivates lighting and fans, optimizing energy consumption in real-time. The methodology follows the Research and Development (R&D) framework, encompassing four stages: (1) requirement analysis to identify key system functionalities and component specifications, (2) system design using flowcharts and block diagrams to outline hardware-software integration, (3) hardware assembly involving Arduino Uno, PIR sensors, and relay modules, and (4) functional testing for validating system accuracy in real-world conditions, specifically in human detection range and energy efficiency. The results indicate that the proposed system achieves an 8-meter detection range with high accuracy, aligning well with existing technologies in energy management for enclosed spaces. Compared to similar systems that utilize alternative microcontrollers or sensors, the Arduino Uno-based approach offers a cost-effective solution with comparable detection reliability and reduced energy waste, suitable for both residential and small commercial applications. The system’s capability to consistently reduce electricity consumption highlights its practical application in energy-saving initiatives, particularly within the context of increasing global energy demands. This research demonstrates that automated systems using accessible microcontroller technology like Arduino Uno can provide a significant impact in the field of energy-efficient automation.